Solving arithmetic problems as space for producing diversity - Χρονάκη Άννα (The Greek Review of Social Research, 2012)
The present study discusses how knowledge development relates to «diversity production» within the context of solving arithmetic problems. The study focuses on analyzing the interaction amongst two Roma girls and their teacher. Problem solving is considered as a social practice in the everyday of school community and as an integral part of children’s mathematical literacy. The analysis here, although based on data discussed in previous studies (see Χρονάκη, 2003• Chronaki, 2003, 2004), focuses on the mediated role played by «arithmetic» itself as part of performing and negotiating identities in the Greek school community and as part of the developing interaction amongst girls and their teacher.